Long-term radiocaesium cycling in forest ecosystems - Itthipoonthanakorn, Thawatchai (2018)
This study focused on the long-term cycling of radiocaesium in pine forests at Boundary Plantation (Sherwood Forest, England), Chernobyl (Ukraine) and Wat Ban Chan in northern Thailand, each of which received markedly different levels of contamination due to radiocaesium deposition from the atmosphere under different circumstances. Systematic studies were made of stable and radiocaesium, potassium and rubidium in soil horizons, tree stems, needles and throughfall (the latter only at Boundary Plantation). Measurements of total concentrations were complemented with determinations of exchangeable fractions as well as the isotopic exchangeability of radio- and stable caesium. Data from Boundary Plantation and Wat Ban Chan were used to test, validate and calibrate the RIFE (Radionuclides in Forest Ecosystems) model for long-term forecasts of radiocaesium behaviour in forest ecosystems. Finally, modelling of 137Cs migration in forest soils was carried out to describe the relationship between the depth of the forest soil profile and the year of litterfall, to better understand the migration of fallout 137Cs. Boundary Plantation, a forest of semi-natural Corsican pine (Pinus nigra), receives chronic atmospheric fallout from nuclear weapons tests in the 1960s. Forest samples were collected every three months from June 2014 to March 2015 at a 24 randomly located sampling sites. The forest soil has a well-developed surface organic horizon while the mineral soil is composed almost entirely of quartz with no identifiable clay minerals. About 65% of nuclear-weapons fallout 137Cs is distributed within the organic layer (upper 9 cm) and maximum of vertical distribution is 12.9% at 8 cm depth. The accumulation of well-decomposed organic matter in the middle of the organic layer is strongly related to the migration of 137Cs in the soil; modelling describes the relationship between the depth of organic matter accumulating in the upper part of the forest soil profile and the year of litterfall indicates that fallout 137Cs deposited in 1963 has migrated in tandem with organic matter at the same rate of migration from the surface. Soil pH also appears to play a key role in controlling the mobility of Cs isotopes, with the most acidic layers within the soil organic horizons holding the highest 137Cs activity concentrations and having the highest exchangeable 133Cs concentrations. Wat Ban Chan in Thailand is a native tropical forest of Pinus kesiya (or Three-needled pine) which received chronic distribution of atmospheric fallout from nuclear weapons tests in the 1960s. Samples were taken from this site in late February 2016 at six randomly located co-ordinates. The forest soil is typical of similar forest soils in the tropical zone. The organic matter, even at the surface, is much less abundant than in temperate forest soils while the mineral soil is composed almost entirely of quartz with no identifiable clay minerals. About 84% of nuclear weapons fallout 137Cs is distributed within the upper 3 cm and the maximal distribution is 37.6% at 2 cm depth. Even though the organic matter content in the upper 2 – 3 cm of the soil profile is low it probably still plays an important role in the vertical distribution of 137Cs. The variation of soil pH throughout the upper 13 cm of the soil profile is less than 1 pH unit and thus is unlikely to influence the vertical distributions of 137Cs and 133Cs in the soil. K and Rb are strong competitors of Cs during cycling within the forest ecosystems at Boundary Plantation and Wat Ban Chan. K is present in the exchangeable fraction in soil at much higher concentration than Rb and especially Cs. The overall degree of translocation from soil to needles is in the order of 39K > 85Rb > 133Cs. Forest sites surrounding the Chernobyl nuclear power plant in Ukraine received acute and localised deposition of nuclear fallout during the Chernobyl reactor accident in April and May 1986. Samples were taken from four Scots pine (Pinus sylvestris L.) plantations close to Chernobyl in early September 2015. Tree cores were taken at all four sites (Red Forest, North Trace, Kopachi and Bourakovka). Soil cores were also collected at Kopachi where 137Cs behaviour appears similar to 133Cs as indicated by Tag values of 133Cs and 137Cs. Scots pine at the Red Forest and the North Trace sites were exposed to extremely high and acute radiation doses (more than 5.0 mGy/h) in the very early stages of the Chernobyl accident. The surviving Scots pine trees sampled in 2015 show a transient decrease in growth rate for several years after 1986, and then show signs of accelerated growth possibly due to a reduction in competition from surrounding trees (an effect known to foresters as ‘growth release’). Calculations of present day 137Cs distributions using the RIFE model for Boundary Plantation and Wat Ban Chan calibrated with inter-compartmental half-times from seven European (‘SEMINAT’) forest sites proved surprisingly accurate, although the model consistently under- and over-predicted the percentage of the total 137Cs inventories retained in the organic and mineral soil layers, respectively. Site-specific calibrations of the RIFE model were made using newly acquired data for nuclear weapons 137Cs deposited in 1963 at Boundary Plantation and Wat Ban Chan. It is considered that these calibrations are more applicable for long-term predictions of radiocaesium cycling in forests than the SEMINAT calibrations which were based on measurements made less than 10 years after the Chernobyl accident in 1986. Finally, measured unsupported 210Pb activities in forest soil profiles were modelled to describe the relationship between the accumulating depth of organic matter in the forest soil profile and the year of litterfall, to improve understanding of the migration of fallout 137Cs at Boundary Plantation (Sherwood Forest, UK) and in the relatively organic-poor soil at Wat Ban Chan in Thailand.